2009
DOI: 10.1007/s00167-009-0831-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of mechanoreceptors in the tibial remnant of the ruptured anterior cruciate ligament in human knees

Abstract: This study was performed to identify the mechanoreceptors in the tibial remnants of ruptured human anterior cruciate ligaments (ACL) by immunohistochemical staining. Thirty-six specimens of tibial ACL remnants were obtained from patients with ACL ruptures during arthroscopic ACL reconstruction. As control, two normal ACL specimens were taken from healthy knee amputated at thigh level due to trauma. The specimen was serially sectioned at 40 mum. In control group, the average number of sections per specimen was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 31 publications
2
79
1
Order By: Relevance
“…**P \ .01 (n = 6 in each group). 10,27. Immunofluorescent staining for neurofilament demonstrated an enhancement of proprioceptive recovery in animals treated with ACL augmentation in contrast to that observed in the reconstruction group (Figure 5, A and B).…”
contrasting
confidence: 51%
“…**P \ .01 (n = 6 in each group). 10,27. Immunofluorescent staining for neurofilament demonstrated an enhancement of proprioceptive recovery in animals treated with ACL augmentation in contrast to that observed in the reconstruction group (Figure 5, A and B).…”
contrasting
confidence: 51%
“…Thus to preserve or to ensure the innervation of the reconstructed ACL should be a main scope of ACR reconstructive surgery [4][5][6]. Sensory innervation is absent from reconstructed ACL [7,21]while innervation has been demonstrated in grafts inserted in ACL remnants [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this hypothesis is still not supported by clinical findings [15]. In patients with cruciate-retaining total knee arthroplasty mechanoreceptors are present 5 to 12 years later [16], and residual remnants of ruptured ACL contain morphologically normal mechanoreceptors and proprioceptive fibbers evenly distributed at both tibial and femoral attachments in one third of the cases [17][18][19][20]. Conversely, other researchers reported the absence of mechanoreceptors in biopsy samples of ACL after reconstruction with Achilles allografts (1 to 10 years), and absence of sensory function after ACL re-construction, presumably because the ACL grafts were not reinnervated [7,21].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mechanoreceptors in the ACL has led several authors to suppose that these receptors influence motor function and, conversely, that their loss leads to dysfunction. 5 A study has reported that knee proprioception, rather than clinically satisfactory mechanical restoration, is more closely related to both the REMNANT PRESERVATION e333 functional outcome and patient satisfaction after ACL reconstruction. 6 Preservation of the ACL remnant as a biological sleeve for the graft is an important issue from the viewpoints of acceleration of revascularization and ligamentization, preservation of the proprioceptive nerve fibers, enhancement of the biological environment for healing, and maintenance of the anchor point at the native tibial attachment, in addition to yielding a lower incidence of tibial bone tunnel enlargement.…”
Section: Discussionmentioning
confidence: 99%